Application of Repairing Agitator Mixer Tank in Watertreatment Technology as an Effort to Improve the Quality of Processing River Water to Make it Clean - Aris Puja Widikda; Farid Mujayyin; Rizkiyah Nur Putri (Cita Konsultindo Research Center, 2024)
Water is a source of our daily lives, both to meet the needs of society and industry. We all agree that there is an opinion that states that water is a necessity that cannot be replaced by other goods. In reality, currently the real conditions are at an alarming stage if not critical, both in terms of water quantity and quality. If this condition is left untreated and not anticipated from now on, it will become a potential conflict and disaster for industrial society in particular. The limited supply of water resources and the challenges of managing water in accordance with sustainability are very necessary. Handling problems in the water resources sector, such as reservoir or dam infrastructure for water sources, river water management, water purification, in the future, if not done immediately, could have an impact on disrupting human activities and welfare, so that in the future it requires comprehensive handling. Problems with river water processing in the water treatment area are based on observations of brownish water color, pH values ​​above 9 mg/l, water quality not in accordance with established standards. Based on interviews with water treatment duty officers, the turbidity of the water is caused by particles suspended in the water which causes the water to look cloudy, dirty, even as if there is mud deposits. According to the procedure for the purification storage tank, chemical mixing has been added to the chemical tank. After being identified in the field, the electric motor driving force as the energy source and the gearbox used to reduce the rotation speed to only 60 (Rpm) experienced a slowdown in stirring in the mixer agitator so that the coagulation process was slow so that the solid particles in the water content formed less than perfect flocs. Method of solving problems in water treatment with efforts to improve component settings with the aim of improving the standard operational performance of water treatment procedures and maintenance procedures such as setting speed and improving the stirring power of the agitator mixer by rotating the impeller which was initially not mixed evenly, it is hoped that the chemicals and water will react perfectly so that the water becomes clear. The results of improvements and settings on the water treatment components show that the water pH level has increased and the quality of water clarity has reached 7.71 NTUs.